2021
DOI: 10.1186/s12875-021-01472-2
|View full text |Cite
|
Sign up to set email alerts
|

Is therapeutic inertia present in hyperglycaemia, hypertension and hypercholesterolaemia management among adults with type 2 diabetes in three health clinics in Malaysia? a retrospective cohort study

Abstract: Background Good-quality evidence has shown that early glycaemic, blood pressure and LDL-cholesterol control in people with type 2 diabetes (T2D) leads to better outcomes. In spite of that, diseases control have been inadequate globally, and therapeutic inertia could be one of the main cause. Evidence on therapeutic inertia has been lacking at primary care setting. This retrospective cohort study aimed to determine the proportions of therapeutic inertia when treatment targets of HbA1c, blood pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
1
7
1
Order By: Relevance
“…A Malaysian study showed that while the majority of clinicians used dyslipidaemia guidelines, there were wide variation in their practice with some clinicians did not prescribe based on the guidelines [ 41 ]. Furthermore, another study reported a high proportion of therapeutic inertia for LLM (61%), which resulted in lower odds of achieving LDL-c target [ 42 ]. Various factors have been proposed to contribute to treatment inertia, including physician’s fear of side effects, as well as the availability of appropriate medications [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Malaysian study showed that while the majority of clinicians used dyslipidaemia guidelines, there were wide variation in their practice with some clinicians did not prescribe based on the guidelines [ 41 ]. Furthermore, another study reported a high proportion of therapeutic inertia for LLM (61%), which resulted in lower odds of achieving LDL-c target [ 42 ]. Various factors have been proposed to contribute to treatment inertia, including physician’s fear of side effects, as well as the availability of appropriate medications [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another study reported a high proportion of therapeutic inertia for LLM (61%), which resulted in lower odds of achieving LDL-c target [ 42 ]. Various factors have been proposed to contribute to treatment inertia, including physician’s fear of side effects, as well as the availability of appropriate medications [ 42 ]. Inappropriate prescriptions were also observed in a previous study in the United Kingdom where most patients were initiated on statins without global CVD risk assessments, and some overtreatment also occurred in the low-risk patients [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“… 31 Several studies have reported on possibility of inertia for therapeutic intensification in NCDs. 32 , 33 Studies have reported on physicians' dilemma in intensification in apparently healthy individuals 4 or fears of affecting the patient's delicate life balance. 34 …”
Section: Discussionmentioning
confidence: 99%
“…10 At public health clinics treating 522 persons with type 2 diabetes in Malaysia, therapeutic inertia in increasing glucose-lowering treatment was seen in up to 64% of visits, in increasing antihypertensive treatment in 51%, and in increasing LDL cholesterollowering treatment in 61% of visits. 11 Approaches to address therapeutic inertia are limited. In a meta-analysis of 36 studies of interventions by nonphysician providers such as nurses, certified diabetes educators, and pharmacists to address therapeutic inertia in glycemic management, effective HbA1c reduction was only demonstrated at levels ≥9% and demonstrating reductions far from attaining desirable levels.…”
mentioning
confidence: 99%
“… 10 At public health clinics treating 522 persons with type 2 diabetes in Malaysia, therapeutic inertia in increasing glucose‐lowering treatment was seen in up to 64% of visits, in increasing antihypertensive treatment in 51%, and in increasing LDL cholesterol‐lowering treatment in 61% of visits. 11 …”
mentioning
confidence: 99%